Analysis of coal mining impact model based on HMM model - Li Weilong; Wang Qing; Liu Xin; Zhang Canming (Dianzi Jishu Yingyong, 2022)
In view of the safety problem of rock burst in coal production and mining, an assessment and analysis of coal mining impact model based on hidden Markov(HMM) model was proposed. Data samples collected under normal and abnormal conditions in coal mining environment were selected as offline training samples to obtain parameters of pre-mining environment model. Then through real-time detection of coal mining data samples as online training samples, real-time data is sent to the pre-mining environment model for evaluation, and the maximum probability is obtained according to the maximum likelihood learning, and the current operating state of the system is obtained through matching. The experimental results show that the model has high reliability in the coal mining impact and the coal safety monitoring work is stable.